The Influence of Investment Education, Risk Perception, and Technological Advances on Students' Interest in Stock Investment - Susanto, Rio (Open Access Indonesia Journal of Social Sciences, 2024)
Investment is a commitment of a certain amount of funds or other resources made at this time, with the aim of obtaining a number of profits in the future. According to sukirno, investment activities carried out by the community continuously will increase economic activity and employment opportunities, increase national income and raise the level of prosperity of society. Investment interest is the desire to find out about investment starting from the type, advantages, disadvantages, investment performance and so on. This research was conducted to determine the influence of investment education, risk perception and technological advancement on students' interest in stock investment. Researchers used the slovin formula to determine the number of samples used in the research, with a total sample of 62 respondents. The research method uses multiple linear regression, classical assumption test, validity test, reliability test and t test. The research results show that investment education, risk perception and technological advances have no effect on students' interest in investing in shares.